Tuberculose pleural no Estado de Roraima no período de 2005-2013: perfil epidemiológico e qualidade diagnóstica - Machado, Tao (2014)
Tuberculosis is among the ten main causes of death in the world and Brazil is one of 22 countries that account for 80 % of the global burden of disease. Pleural presentation, the main object of this study, is the most common extrapulmonary TB form in HIV-seronegative individuals and always appears as a differential diagnosis to be considered in patients with pleural effusions. The main objective was to know the quality of diagnoses and the epidemiological profile of patients with pleural tuberculosis in the state of Roraima aiming to offer a technical foundation to public policies destined to fight the disease. The diagnosis of pleural tuberculosis is based primarily on the identification of Mycobacterium tuberculosis on direct examination or culture of pleural fluid or pleural tissue fragment, as well as in the presence of granuloma on histopathological analysis of the tissue sample. The present study was designed as a qualitative and quantitative transversal research to evaluate the diagnostic criteria being used and the determinants of pleural disease presentation in the state of Roraima, located in northern Brazil, within the limits of the Amazon, and with extensive socio-cultural and environmental diversity. This is an observational, retrospective and descriptive study based on a review of secondary SINAN data, including all cases of pleural tuberculosis reported from 2005 to 2013. Of 1.395 reported cases of tuberculosis in the period, 8.3% were of pleural presentation, totaling 38.9% of extrapulmonary cases in the sample. The incidence rate of this presentation did not follow the downward trend of pulmonary tuberculosis in the period. The prevalence of quality diagnosis was found to be 28.5 % (95% CI: 20.4 to 37.6 %), and in a univariate analysis, no variable among the possible clinical and demographic characteristics searched in the data basis had significant impact in the quality of the diagnosis. The main conclusion of the study indicates the need for a specific referral policy at a state level in order to facilitate access to diagnostic methods recommended by the National Tuberculosis Control Programme available in the health system.